Sectoral heterogeneity in patterns of educational mismatch in tourism: a gender comparison - Lasso-de-la-Vega, Elena; Campos-Soria, Juan Antonio; García-Pozo, Alejandro (My University, 2022)
The study of the effects of educational mismatch has shown this phenomenon to generate inefficiencies due to a misallocation of resources. These inefficiencies are more detrimental for countries such as Spain, where education is financed to a large extent with public funds, and low-skill demanding sectors, such as tourism, have a high weight in the economy. This paper aims to study the determinants of educational mismatch from a gender perspective, analysing the sectoral heterogeneity that may arise among these determinants in four key productive branches within the Spanish tourism sub-sector, i.e., hotels, transport, intermediary services and other complementary services. For this purpose, a multinomial logit model is employed, which will be estimated separately for each sector and gender of interest, using data from the 2018 Wage Structure Survey of the Spanish National Statistics Institute. Among the results obtained, it is highlighted, firstly, that educational mismatch is not a transitory phenomenon given that it occurs both at the beginning of the individual's working career and at very different levels of permanence. Secondly, it is interesting to note the greater probability of male overeducation observed in the hotel and catering industry and female overeducation in the rest of the services analysed, the latter result possibly reflecting the occupational gender segregation experienced by women in these branches of the economy.
Keywords: Educación y empleo; Educational mismatch; Gender; Determinants; Tourism; Sectoral comparison